English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please show steps

2006-11-13 07:26:34 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

assuming your expression equals 0
x^2-25-0
(x+5)(x-5)=0
x=5 or -5

2006-11-13 07:28:50 · answer #1 · answered by Greg G 5 · 0 0

5=x

2006-11-13 07:31:27 · answer #2 · answered by Anonymous · 0 0

I assume you mean x2 - 25 = 0
So x2 = 25
Then x=5

2006-11-13 07:29:49 · answer #3 · answered by daniel_cohadier 3 · 0 0

x^2-25=0
x^2=25
x= +-5

2006-11-13 07:28:56 · answer #4 · answered by      7 · 0 0

x^2-25=(x+5)(x-5)
do you want the roots?
they are x-5=0
x=5
x+5=0
x=-5

2006-11-13 07:30:54 · answer #5 · answered by yupchagee 7 · 0 0

Uh, nope. I don't know the answer. Sorry

2006-11-13 07:28:02 · answer #6 · answered by ♦♦pixiechix♦♦ 5 · 0 0

fedest.com, questions and answers